Digital work platform: Understanding platforms, workers, clients in a service relation - Cruz, Sofia Alexandra; Gameiro, Ana (Frontiers in Sociology, 2023)
The rapid growth of digital economic activity had led to considerable scholarly interest in the phenomenon of platforms. Evidence shows how digital work platforms constitute one of the most relevant changes that have occurred in recent years and assume the condition of actors with an important presence in national and global work markets. However, these changes cannot be understood by focusing only on the work sphere, as the sphere of consumption is also central to this debate. In fact, the new ways of organising, dividing and coordinating work on digital platforms are interconnected with specific modalities of consumption of the services made available by them. This article argues that a service relation approach allows an understanding of what is happening on digital work platforms, both in terms of the structural and conjunctural configurations of the interrelationships between platforms, workers and clients, as well as their social and economic consequences. This approach allows the analysis of the web of interdependencies between distinctive types of platforms, workers and clients, and to discuss how changes longitudinally within it are conditioned by the very transformations inherent to the platforms market. Thus, future research needs to explore the network of the voices of platforms, workers and clients in order to produce a robust analysis of these triangular relations as well as of the challenges regarding the differences and interconnections between algorithmic and human management.